Solid-state composite negative electrode structure and preparation method thereof and sulfide all-solid-state battery

By forming a "sandwich" structure of lithium metal-reaction layer-buffer layer on the surface of lithium metal, the interface problem between the lithium metal anode and the sulfide solid electrolyte is solved, achieving uniform lithium ion deposition and suppression of volume expansion, thus improving the cycle life and performance of the sulfide all-solid-state battery.

CN116581246BActive Publication Date: 2026-11-06ENPOWER (PEKING) INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310777366.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2026-11-06
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

Interface problems between the lithium metal anode and the sulfide solid electrolyte lead to uneven lithium-ion deposition, side reactions, lithium dendrite growth, and volume expansion, hindering the commercialization of sulfide all-solid-state batteries.

Method used

A buffer layer of lithium metal and lithium-affinity material is coated on the surface of lithium metal. The lithium metal-reaction layer-buffer layer "sandwich" structure is formed by pressing. The buffer layer material forms an alloy layer with the lithium metal, which improves the interfacial contact and inhibits the growth of lithium dendrites.

Benefits of technology

It effectively reduces interface resistance, decreases electrolyte consumption, improves battery cycle stability and rate performance, and increases cycle life by more than 3 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116581246B_ABST
    Figure CN116581246B_ABST
Patent Text Reader

Abstract

This invention provides a solid-state composite anode structure, its preparation method, and a sulfide all-solid-state battery using it as the anode. The solid-state composite anode structure includes lithium metal, a buffer layer covering at least one surface of the lithium metal, and a reaction layer located between the lithium metal and the buffer layer. The buffer layer includes a lithium-intercalating material and a lithiophilic material. The reaction layer is an alloy layer formed by the reaction of the buffer layer and lithium metal during the pressing process. This invention, by modifying the lithium anode with lithium-intercalating and lithiophilic materials combined with a pressing process, produces a dense solid-state composite anode with a lithium metal-reaction layer-buffer layer "sandwich" structure, reducing the volume expansion of the lithium anode during cycling and improving the cycle stability and rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sulfide solid-state lithium battery technology, and relates to a solid-state composite anode structure, its preparation method, and a sulfide all-solid-state battery. Background Technology

[0002] As people's requirements for high energy density and high safety of batteries continue to increase, using solid electrolytes with lithium metal anodes has become an ideal choice. Among these, sulfide solid electrolytes have attracted much attention due to their excellent ionic conductivity and good machinability.

[0003] However, interface problems exist between the lithium metal anode and the sulfide solid electrolyte in practical use: 1. The uneven solid-solid contact interface between lithium metal and sulfide solid electrolyte leads to uneven deposition of lithium ions; 2. After direct contact between lithium metal and sulfide electrolyte, side reactions occur during charging and discharging, causing byproducts to accumulate at the interface, which increases the interface impedance and causes uneven local current density distribution; 3. The severe volume expansion of lithium metal during cycling further deteriorates the interface; These factors seriously hinder the commercialization of sulfide all-solid-state batteries.

[0004] Therefore, suppressing the growth of lithium dendrites and improving the anode interface of sulfide solid-state batteries has become an urgent problem to be solved. Summary of the Invention

[0005] To address the problems existing in the prior art, this invention provides a solid-state composite anode structure, its preparation method, and a sulfide all-solid-state battery. This invention produces a solid-state composite anode by dry-coating an inorganic powder composed of a lithium-intercalating material and a lithiophilic material onto the surface of metallic lithium, followed by pressing. This anode possesses a unique lithium metal-reaction layer-buffer layer "sandwich" structure. The reaction layer significantly increases the contact strength between the buffer layer material and the lithium metal, effectively reducing the interfacial resistance. The buffer layer, on the one hand, isolates the electrolyte from direct contact with the lithium metal, reducing electrolyte consumption; on the other hand, during cycling, the buffer layer material and the lithium metal react in situ to form an alloy layer, improving the interface between the sulfide solid electrolyte and the lithium anode. Specifically, the lithiophilic material can induce uniform lithium-ion deposition during cycling, inhibiting lithium dendrite growth; the lithium-intercalating material can embed some lithium during cycling, reducing the volume expansion of the lithium anode during cycling and improving the battery's cycle stability and rate performance.

[0006] To achieve this objective, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a solid-state composite anode structure, the solid-state composite anode structure comprising lithium metal, a buffer layer covering at least one surface of the lithium metal, and a reaction layer located between the lithium metal and the buffer layer, the buffer layer comprising a lithium-intercalating material and a lithium-affinity material, and the reaction layer being an alloy layer formed between the buffer layer and the lithium metal during the pressing process.

[0008] As a preferred embodiment of the present invention, the average particle size of the lithiophilic material is D50 < 60 nm.

[0009] As a preferred embodiment of the present invention, the lithiophilic material includes any one or a combination of at least two of metal oxides, metal sulfides, or metal chlorides.

[0010] As a preferred embodiment of the present invention, the lithiophilic material includes any one or a combination of at least two of zinc oxide, zinc sulfide, zinc chloride, aluminum oxide, magnesium oxide, tin oxide or copper oxide, preferably zinc oxide and / or zinc chloride.

[0011] As a preferred embodiment of the present invention, the average particle size of the lithium intercalation material is D50 < 600 nm.

[0012] As a preferred embodiment of the present invention, the lithium intercalation material includes any one or a combination of at least two of graphite, silicon, or carbon nanotubes, preferably graphite and / or carbon nanotubes.

[0013] As a preferred embodiment of the present invention, the reaction layer is a Li / M and Li / N alloy generated in situ during the cycling process of lithium metal and buffer layer material, wherein M is element C and / or Si, and N is any one or a combination of at least two of metals Zn, Al, Mg, Sn or Cu.

[0014] As a preferred embodiment of the present invention, when M is element C, the lithiation product of metallic lithium and the lithium-intercalated material is Li. x C y Where x:y = 1:1 to 1:24, preferably x:y = 1:1 to 1:6; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 to 1:4, preferably m:n = 1:1 to 1:1.5.

[0015] Preferably, when M is element Si, the lithiation product of the lithium metal and the lithium-intercalated material is Li. x Si, wherein x = 0 to 4.4, preferably x = 0.5 to 3.25; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 to 1:4, preferably m:n = 1:1 to 1:1.5.

[0016] As a preferred embodiment of the present invention, the ratio of element N in the reaction layer and the buffer layer is x:y = 1:1 to 1:5, preferably x:y = 1:1 to 1:3; the ratio of element M is m:n = 1:1 to 1:3, preferably m:n = 1:1 to 1:2.

[0017] As a preferred embodiment of the present invention, the lithium metal includes any one of lithium sheets, lithium foils, or lithium strips.

[0018] As a preferred embodiment of the present invention, the mass ratio of the lithium-intercalating material to the lithium-affinity material is 1:(1-20), preferably 1:(2-10).

[0019] Secondly, the present invention provides a method for preparing the aforementioned composite lithium metal anode, the method comprising the following steps:

[0020] A solid composite anode is obtained by coating a mixture of lithium-intercalating and lithium-affinity materials onto one surface of metallic lithium and then pressing it.

[0021] Alternatively, a mixture of lithium-intercalating and lithium-affinity materials can be coated onto one surface of lithium metal and pressed, then coated onto the other surface of lithium metal and pressed again to obtain a solid composite anode with a buffer layer.

[0022] As a preferred embodiment of the present invention, the mass ratio of the lithium-intercalating material to the lithium-affinity material is 1:(1-20), preferably 1:(2-10).

[0023] As a preferred embodiment of the present invention, the mixing is any one of ball milling, stirring, or vibration mixing.

[0024] As a preferred embodiment of the present invention, the ball milling speed is 2 r / min-300 r / min, preferably 80 r / min-120 r / min.

[0025] As a preferred embodiment of the present invention, the ball milling time is 2 min to 360 min, preferably 30 min to 60 min.

[0026] As a preferred embodiment of the present invention, the coating method includes any one or a combination of at least two of the following: scraping, rolling, or brushing.

[0027] As a preferred embodiment of the present invention, the coating is performed under an inert atmosphere.

[0028] As a preferred embodiment of the present invention, the inert atmosphere includes any one or a combination of at least two of helium, neon, argon, krypton, or xenon.

[0029] As a preferred embodiment of the present invention, the coating thickness of the mixture on the lithium metal surface is 1μm-10μm.

[0030] As a preferred embodiment of the present invention, the mass ratio of the mixture to lithium metal is (10-100):1, preferably (50-100):1.

[0031] As a preferred embodiment of the present invention, the pressing method is any one or a combination of at least two of roller pressing, extrusion or rolling.

[0032] As a preferred embodiment of the present invention, the pressure of the pressing process is 1MPa-20MPa, preferably 1MPa-5MPa.

[0033] As a preferred embodiment of the present invention, the pressing time is 5s-100s, preferably 10s-50s.

[0034] As a preferred embodiment of the present invention, the pressing process is carried out under an inert atmosphere.

[0035] As a preferred embodiment of the present invention, the inert atmosphere includes any one or a combination of at least two of helium, neon, argon, krypton, or xenon.

[0036] Thirdly, the present invention provides a sulfide all-solid-state battery, wherein the negative electrode in the sulfide all-solid-state battery is the aforementioned solid-state composite negative electrode.

[0037] As a preferred embodiment of the present invention, the sulfide all-solid-state battery includes a positive electrode material, a negative electrode material, and a sulfide solid electrolyte disposed between the positive electrode and the negative electrode, wherein the negative electrode is the aforementioned solid composite negative electrode, and the active material of the positive electrode is any one or a combination of at least two of layered oxides, polyanionic active materials, lithium-rich oxides, or spinel oxides.

[0038] As a preferred embodiment of the present invention, the layered oxide includes LiNi. 1-x-y Co x Mn y O2 and / or LiNi 1-x- y Co x Al y O2, where x = 0 to 1, y = 0 to 1.

[0039] As a preferred embodiment of the present invention, the polyanionic active material includes any one or a combination of at least two of LiFePO4, LiMnPO4, or LiCoPO4.

[0040] As a preferred embodiment of the present invention, the lithium-rich oxide includes Li2MnO3 and / or Li2RuO3.

[0041] As a preferred embodiment of the present invention, the spinel oxide includes LiMn2O4 and / or LiNi. 0.5 Mn 1.5 O2.

[0042] As a preferred embodiment of the present invention, the sulfide solid electrolyte includes nLi2S-(100-n)P2S5, Li6PS5X, and Li 11-a M 2-a P 1+a S 12 Any one or at least two of the following; where n = 0 to 100; a = 0 to 2; X is any one or at least two of Cl, Br, or I; M is any one or at least two of Ge, Sn, or Si.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] This invention premixes lithium-intercalating and lithium-affinity materials and then coats them onto the surface of metallic lithium through a pressing process to produce a dense solid-state composite anode. The unique lithium metal-reaction layer-buffer layer "sandwich" structure demonstrates a multifunctional protection strategy. The reaction layer significantly increases the contact strength between the buffer layer material and the lithium metal, effectively reducing the interface resistance. The buffer layer isolates the electrolyte from direct contact with the lithium metal, reducing electrolyte consumption. Furthermore, during cycling, the buffer layer material and the lithium metal react in situ to form an alloy layer, improving the interface between the sulfide solid electrolyte and the lithium anode. Specifically, the lithium-affinity material can induce uniform lithium-ion deposition during cycling, inhibiting the growth of lithium dendrites; the lithium-intercalating material can embed some lithium during cycling, reducing the volume expansion of the lithium anode during cycling, thus increasing the cycle life of the all-solid-state battery by more than 3 times.

[0045] Furthermore, the method described in this invention employs a dry method to coat lithium-metal surfaces with lithium intercalation materials and lithium-affinity materials through pressing, eliminating the need for template agents. This method is simple, feasible, and provides stable technical results, making it suitable for industrial applications. Attached Figure Description

[0046] Figure 1 This is a schematic diagram of the lithiophilicity characterization of the solid composite negative electrode prepared in this invention, where (a) is the contact angle of the solid electrolyte LPSC1 and (b) is the contact angle of the solid composite negative electrode.

[0047] Figure 2 The images shown are electron microscope images of the cross-section of the lithium buffer layer in the solid composite anode structure prepared in Example 7, where (a) is a morphological characterization image of the lithium buffer layer and (b) is a cross-sectional image of the lithium buffer layer showing the distribution of C and Zn elements.

[0048] Figure 3 This is an electron microscope image of the longitudinal section of the lithium buffer layer in the solid composite anode structure prepared in Example 7;

[0049] Figure 4 This is a schematic diagram of the structure of the sulfide all-solid-state battery prepared in Example 7, wherein 1-positive electrode, 2-solid electrolyte, and 3-solid composite negative electrode.

[0050] Figure 5 This is a schematic diagram of the solid composite anode structure prepared in Example 7, where 4-buffer layer, 5-reaction layer, and 6-lithium metal;

[0051] Figure 6 This is a comparative graph showing the cycle performance of the sulfide all-solid-state batteries of Example 7 and Comparative Example 1. Detailed Implementation

[0052] To better illustrate the present invention and facilitate understanding of its technical solutions, the present invention will be further described in detail below. However, the following embodiments are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0053] The specific embodiments of the present invention provide a solid-state composite anode structure, which includes lithium metal, a buffer layer covering at least one surface of the lithium metal, and a reaction layer located between the lithium metal and the buffer layer, i.e., a "sandwich" structure of lithium metal-reaction layer-buffer layer. The buffer layer includes a lithium intercalation material and a lithium-affinity material, and the reaction layer is an alloy layer formed between the buffer layer and the lithium metal during the pressing process.

[0054] The solid-state composite anode structure described in this invention, namely the lithium metal-reaction layer-buffer layer "sandwich" structure, has two significant features: firstly, the integrity and stability of the structure; and secondly, the protection provided by the alloy layer formed in situ during the cycling process of the buffer layer material. After pressing, the lithium metal reacts with the buffer layer material to form an alloy layer, effectively increasing the bonding strength between the two, reducing the interfacial resistance, and ensuring the integrity and stability of the structure. Furthermore, the buffer layer is composed of a lithium-intercalating material and a lithium-affinity material. The lithium-intercalating material effectively suppresses the volume expansion of lithium metal and can effectively isolate the solid electrolyte from direct contact with lithium metal, avoiding the consumption of the solid electrolyte. The lithium-affinity material induces uniform lithium deposition and inhibits the growth of lithium dendrites. On the other hand, both the selected lithium-intercalating and lithium-affinity materials can react with metallic lithium to form an alloy layer in situ, effectively isolating the electrolyte from direct contact with lithium metal, constructing a good anode interface, greatly improving the stability of the anode interface, and extending the cycle life of the solid-state battery.

[0055] As a preferred embodiment of the present invention, the average particle size of the lithiophilic material is D50 < 60 nm, such as 55 nm, 50 nm, 45 nm, 40 nm, 35 nm, 30 nm, 25 nm, 20 nm or 15 nm, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0056] As a preferred embodiment of the present invention, the lithiophilic material includes any one or a combination of at least two of metal oxides, metal sulfides, or metal chlorides.

[0057] As a preferred embodiment of the present invention, the lithiophilic material includes any one or a combination of at least two of zinc oxide, zinc sulfide, zinc chloride, aluminum oxide, magnesium oxide, tin oxide or copper oxide, preferably zinc oxide and / or zinc chloride.

[0058] In this invention, the interfacial wettability between the sulfide electrolyte and lithium metal is greatly improved by using a lithiophilic material. The lithium melting contact angle is changed from 180° to 90°, which can effectively induce uniform lithium deposition and play a good role in inhibiting the growth of lithium dendrites.

[0059] Specifically, the lithiophilicity of lithiophilic materials can be tested using the following method: Powdered material is pressed into a sheet shape under a certain pressure, dried, and then molten lithium metal is dropped onto one side of the lithium buffer layer. The contact angle is then measured using a specialized instrument for measuring the surface contact angle. The contact angle is defined as the angle between the interface point of the solid, liquid, and gas phases and the tangent at the liquid-gas interface.

[0060] The lithiophilicity of the composite lithium metal anode prepared in this invention and the molten lithium contact angle of the electrolyte material LPSC1 were characterized as follows: Figure 1 As shown, the composite metal anode in this invention has a smaller contact angle with molten lithium, indicating better lithium affinity.

[0061] As a preferred embodiment of the present invention, the average particle size of the lithium intercalation material is D50 < 600 nm, such as 550 nm, 500 nm, 450 nm, 400 nm, 350 nm, 300 nm, 250 nm, 200 nm or 150 nm, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0062] As a preferred embodiment of the present invention, the lithium intercalation material includes any one or a combination of at least two of graphite, silicon, or carbon nanotubes, preferably graphite and / or carbon nanotubes.

[0063] In a preferred embodiment of the present invention, the reaction layer is a Li / M and Li / N alloy generated by the reaction of lithium metal and buffer layer material during the pressing process, wherein M is element C and / or Si, and N is any one or a combination of at least two of metals Zn, Al, Mg, Sn, or Cu; the reaction equation is as follows:

[0064] Li + M → Li x M y Li + NO → Li m N n

[0065] As a preferred embodiment of the present invention, when M is element C, the lithiation product of metallic lithium and the lithium-intercalated material is Li. x C y Where x:y = 1:1 to 1:24, for example 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, or 1:22, etc., but not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably x:y = 1:1 to 1:6; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 to 1:4, such as 1:1, 1:2, 1:3 or 1:4, but not limited to the listed values. Other unlisted values ​​within this range are also applicable, with m:n = 1:1 to 1:1.5 being the preferred value.

[0066] As a preferred embodiment of the present invention, when M is element Si, the lithiation product of the lithium metal and the lithium-intercalated material is Li. x Si, where x = 0 to 4.4, for example 0.5, 1, 1.5, 2, 2.5, 3, 3.5, or 4, etc., but not limited to the listed values; other unlisted values ​​within this range are also applicable, preferably x = 0.5 to 3.25; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 to 1:4, such as 1:1, 1:2, 1:3 or 1:4, but not limited to the listed values. Other unlisted values ​​within this range are also applicable, with m:n = 1:1 to 1:1.5 being the preferred value.

[0067] As a preferred embodiment of the present invention, the ratio of element N in the reaction layer and the buffer layer is x:y = 1:1 to 1:5, such as 1:1, 1:2, 1:3, 1:4 or 1:5, but not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably x:y = 1:1 to 1:3; the ratio of element M is m:n = 1:1 to 1:3, such as 1:1, 1:2 or 1:3, but not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably m:n = 1:1 to 1:2.

[0068] As a preferred embodiment of the present invention, the lithium metal includes any one of lithium sheets, lithium foils, or lithium strips.

[0069] As a preferred embodiment of the present invention, the mass ratio of the lithium metal to the buffer layer is (10-100):1, for example, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1 or 100:1, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably (50-100):1.

[0070] As a preferred embodiment of the present invention, the mass ratio of the lithium-intercalating material to the lithium-affinity material is 1:(1-20), such as 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18 or 1:20, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 1:(2-10).

[0071] In this invention, the ratio of lithiophilic material to lithium-intercalating material is such that the amount of lithiophilic material is greater than or equal to that of lithiophilic material. This is because the primary purpose of lithiophilic material is to induce uniform lithium-ion deposition, while the secondary purpose of lithiophilic material is to suppress volume expansion.

[0072] The present invention also provides a method for preparing the aforementioned solid-state composite anode structure, the method comprising the following steps:

[0073] A mixture of lithium-intercalating and lithium-affinity materials is coated onto one surface of metallic lithium and then pressed to obtain a solid composite anode.

[0074] Alternatively, a mixture of lithium-intercalating and lithium-affinity materials can be coated onto one surface of lithium metal and pressed, then coated onto the other surface of lithium metal and pressed again to obtain a solid-state composite anode structure.

[0075] The method described in this invention employs a dry process to coat lithium-metal surfaces with lithium intercalation and lithium-affinity materials through pressing. This eliminates the need for template agents and the introduction of additional polymer materials. All components are beneficial to the interface, reducing compositional complexity and uncertainty, and lowering interfacial impedance. Furthermore, the method is simple, feasible, and provides stable technical results, making it suitable for industrial applications.

[0076] As a preferred embodiment of the present invention, the mass ratio of the lithium-intercalating material to the lithium-affinity material is 1:(1-20), such as 1:1, 1:2, 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18 or 1:20, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 1:(2-10).

[0077] As a preferred embodiment of the present invention, the mixing is any one of ball milling, stirring, or vibration mixing.

[0078] As a preferred embodiment of the present invention, the ball milling mixing speed is 2r / min-300r / min, such as 2r / min, 10r / min, 20r / min, 40r / min, 60r / min, 80r / min, 100r / min, 120r / min, 140r / min, 160r / min, 180r / min, 200r / min, 220r / min, 240r / min, 260r / min, 280r / min or 300r / min, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 80r / min-120r / min.

[0079] As a preferred embodiment of the present invention, the ball milling time is 2 min to 360 min, such as 2 min, 10 min, 30 min, 50 min, 60 min, 80 min, 100 min, 130 min, 150 min, 170 min, 200 min, 230 min, 250 min, 270 min, 300 min, 320 min, 340 min, or 360 min, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 30 min to 60 min.

[0080] As a preferred embodiment of the present invention, the coating method includes any one or a combination of at least two of the following: scraping, rolling, or brushing.

[0081] As a preferred embodiment of the present invention, the coating is performed under an inert atmosphere.

[0082] As a preferred embodiment of the present invention, the inert atmosphere includes any one or a combination of at least two of helium, neon, argon, krypton, or xenon.

[0083] As a preferred embodiment of the present invention, the coating thickness of the mixture on the lithium metal surface is 1μm-10μm, such as 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0084] As a preferred embodiment of the present invention, the mass ratio of the mixture to lithium metal is (10-100):1, for example, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1 or 100:1, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably (50-100):1.

[0085] As a preferred embodiment of the present invention, the pressing method is any one or a combination of at least two of roller pressing, extrusion or rolling.

[0086] In this invention, it is necessary to control the pressure and time range of the pressing process. If the pressure and time are too low, the buffer layer material will not be in close contact with the lithium sheet and the alloy layer cannot be fully formed. If the pressure and time are too high, the lithium sheet will stretch too much, which will also cause the buffer layer material to be too dispersed.

[0087] As a preferred embodiment of the present invention, the pressure of the pressing process is 1MPa-20MPa, such as 1MPa, 3MPa, 5MPa, 7MPa, 10MPa, 13MPa, 15MPa, 17MPa or 20MPa, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 1MPa-5MPa.

[0088] As a preferred embodiment of the present invention, the pressing time is 5s-100s, such as 5s, 10s, 20s, 40s, 70s or 100s, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable, preferably 10s-50s.

[0089] As a preferred embodiment of the present invention, the pressing process is carried out under an inert atmosphere.

[0090] As a preferred embodiment of the present invention, the inert atmosphere includes any one or a combination of at least two of helium, neon, argon, krypton, or xenon.

[0091] The specific embodiments of the present invention also provide a sulfide all-solid-state battery, wherein the negative electrode in the sulfide all-solid-state battery is the aforementioned solid-state composite negative electrode.

[0092] As a preferred embodiment of the present invention, the sulfide all-solid-state battery includes a positive electrode material, a negative electrode material, and a sulfide solid electrolyte disposed between the positive electrode and the negative electrode, wherein the negative electrode is the aforementioned solid composite negative electrode, and the active material of the positive electrode is any one or a combination of at least two of layered oxides, polyanionic active materials, lithium-rich oxides, or spinel oxides.

[0093] As a preferred embodiment of the present invention, the layered oxide includes LiNi. 1-x-y Co x Mn y O2 and / or LiNi 1-x- y Co x Al y O2, where x = 0 to 1, y = 0 to 1.

[0094] As a preferred embodiment of the present invention, the polyanionic active material includes any one or a combination of at least two of LiFePO4, LiMnPO4, or LiCoPO4.

[0095] As a preferred embodiment of the present invention, the lithium-rich oxide includes Li2MnO3 and / or Li2RuO3.

[0096] As a preferred embodiment of the present invention, the spinel oxide includes LiMn2O4 and / or LiNi. 0.5 Mn 1.5 O2.

[0097] As a preferred embodiment of the present invention, the sulfide solid electrolyte includes nLi2S-(100-n)P2S5, Li6PS5X, and Li 11-a M 2-a P 1+a S 12 Any one or at least two of the following; where n = 0 to 100; a = 0 to 2; X is any one or at least two of Cl, Br, or I; M is any one or at least two of Ge, Sn, or Si.

[0098] Specifically, the method for preparing the sulfide all-solid-state battery includes: pressing powder-formed positive electrode, electrolyte, and negative electrode sheets, and then pressing them into an all-solid-state battery in the order of positive electrode-electrolyte-negative electrode. This battery effectively improves safety, cycle life, and rate performance.

[0099] The following are typical but non-limiting embodiments of the present invention:

[0100] Examples 1-20:

[0101] The lithium-intercalating material and the lithium-affinity material were mixed evenly by ball milling according to the proportions listed in Table 1 to obtain a composite material. The mixed composite material was dispersed on the surface of a lithium foil and pressed to obtain a solid composite anode. The entire process was carried out under an inert atmosphere.

[0102] The electron microscope image of the cross-section of the lithium buffer layer in the solid composite anode prepared in Example 7 is shown below. Figure 2 As shown. Among them, Figure 2 (a) shows the morphology of the lithium buffer layer. Figure 2 (b) shows the C and Zn element distribution in a cross section of the lithium buffer layer. It can be seen that the two elements C and Zn are densely distributed on the surface of the lithium buffer layer.

[0103] The electron microscope image of the longitudinal section of the lithium buffer layer in the solid composite anode prepared in Example 7 is shown below. Figure 3 As shown, the thickness of the lithium buffer layer is very thin, ranging from 2 to 5 μm.

[0104] Preparation of sulfide all-solid-state batteries:

[0105] The preparation method of the sulfide solid electrolyte is as follows: Take 0.12 mg of LPSCl electrolyte powder and press it into a Teflon tablet mold at a pressure of 250 MPa to obtain an electrolyte layer;

[0106] The preparation method of the positive electrode is as follows: LiNi 0.8 Co 0.1 Mn 0.1 O2, electrolyte powder (LPSCl), and conductive carbon are mixed evenly in a mass ratio of 75:25:2, and then pressed into a Teflon pressing mold under a pressure of 300MPa to obtain the positive electrode sheet of the battery.

[0107] The preparation method of sulfide all-solid-state battery is as follows: the prepared positive electrode sheet is pressed onto one side of the sulfide electrolyte layer under a pressure of 300 MPa, and then a solid composite negative electrode is pressed onto the other side of the electrolyte layer to obtain the sulfide all-solid-state battery. The solid composite negative electrode is the solid composite negative electrode prepared in Examples 1-20, thus obtaining the corresponding sulfide all-solid-state battery.

[0108] The structure of the prepared sulfide all-solid-state battery is as follows: Figure 4 As shown.

[0109] The resulting battery is a mold battery with an electrode active area of ​​1.12 cm². -2 .

[0110] Comparative Example 1:

[0111] This comparative example provides a sulfide all-solid-state battery, which, except for directly using lithium foil as the negative electrode, has the same positive electrode and sulfide solid electrolyte as in Examples 1-20.

[0112] Comparative Example 2:

[0113] This comparative example provides a sulfide all-solid-state battery, which is the same as that in Example 19 except that only lithium intercalation material is added to the solid composite anode.

[0114] Comparative Example 3:

[0115] This comparative example provides a sulfide all-solid-state battery, which is identical to that in Example 19 except that only a lithiophilic material is added to the solid composite anode. Cycle performance tests were conducted on the sulfide all-solid-state batteries prepared using the solid composite anodes obtained in Examples 1-20 and the sulfide all-solid-state batteries in Comparative Examples 1-3. The specific test method was as follows: constant current charging and discharging were performed at 50°C, with a charging / discharging voltage range of 2.8–4.2V and a charging / discharging rate of 0.3C. The initial capacity of the battery was recorded as C0. One full charge and discharge cycle was recorded as one cycle. The charging and discharging process was repeated as described above, and the battery capacity was tested after each cycle until the battery capacity reached 80% of C0 or a short circuit occurred. The number of cycles at this point was recorded.

[0116] The cycle performance test results of the sulfide all-solid-state batteries prepared using the solid-state composite anodes obtained in Examples 1-20 and the batteries in Comparative Examples 1-3 are shown in Table 1.

[0117] Table 1 Battery Cycle Performance Test Results

[0118]

[0119]

[0120] Analysis of battery cycle performance test results:

[0121] (1) Comparison of Examples 1-7 and Comparative Example 1

[0122] Examples 1-7 demonstrate the effect of adding the lithium buffer layer of the present invention to the lithium metal surface of a sulfide all-solid-state battery on improving the cycle performance of the battery. As shown in Table 1, different lithiophilic materials were selected for the composite protective materials in Examples 1-7. Among these, the improvement in cycle life of the sulfide all-solid-state battery was particularly significant when zinc oxide was used as the lithiophilic material. Under 0.3C charging and discharging conditions, the number of cycles before capacity decay to 80% was over 100. In contrast, the sulfide all-solid-state battery in Comparative Example 1, using lithium metal as the negative electrode, only had 33 cycles before capacity decay to 80% under the same charging and discharging conditions. Furthermore, while the number of cycles before capacity decay to 80% was improved compared to the lithium metal negative electrode, it was still inferior to that of the zinc oxide battery, even though other solid composite negative electrodes were used to assemble the sulfide all-solid-state battery.

[0123] Figure 5 The cycle performance of the sulfide all-solid-state batteries of Example 7 and Comparative Example 1 is shown. Figure 5 It can be seen that the cycle performance of Example 7 is significantly better than that of the comparative example.

[0124] (2) Examples 7-10

[0125] Examples 7-10 illustrate the effect of the ratio of lithiated material to lithiophilic material on the cycle performance of sulfide all-solid-state batteries when zinc oxide is used as the lithiophilic material. Table 1 shows that the sulfide all-solid-state battery has the longest cycle life when the ratio of lithiated material to lithiophilic material is 1:5.

[0126] (3) Example 11

[0127] Example 11 shows that when carbon nanotubes are used as lithium intercalation materials, the solid composite anode also significantly improves the cycle life of sulfide all-solid-state batteries. However, compared with this, the improvement in cycle life of sulfide all-solid-state batteries is more significant when graphite is used as lithium intercalation material.

[0128] (4) Examples 7, Examples 12-18

[0129] Examples 7 and 12-18 illustrate the effects of pressure and time used during the pressing process of solid-state composite anodes on the cycle performance of sulfide all-solid-state batteries. Table 1 shows that the optimal pressing pressure is 3 MPa and the optimal time is 20 seconds; when the pressure and time are outside the protected range, the cycle life of the battery is significantly shortened.

[0130] (5) Example 7, Comparative Example 2, Comparative Example 3

[0131] Examples 7, 2, and 3 illustrate the impact of solid-state composite anodes on the cycle performance of sulfide all-solid-state batteries when using either a lithiated or lithiophilic material alone. Table 1 shows that, under the same conditions, the cycle life of the battery is significantly shortened when either the lithiated or lithiophilic material is used alone.

[0132] (6) Examples 7, 19, and 20

[0133] Examples 7, 19, and 20 illustrate the effects of ball milling speed and time on the cycle performance of sulfide all-solid-state batteries when using mixed materials. Table 1 shows that when the ball milling speed and time significantly exceed the given range, the protection effect on the negative electrode is greatly reduced, and the cycle life of the battery is shortened accordingly.

[0134] The applicant declares that the detailed process equipment and process flow of this invention are illustrated through the above embodiments, but this invention is not limited to the above detailed process equipment and process flow, that is, it does not mean that this invention must rely on the above detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the products of this invention, additions of auxiliary components, and selection of specific methods, all fall within the protection scope and disclosure scope of this invention.

Claims

1. A solid-state composite anode structure, characterized in that, The solid-state composite anode structure includes lithium metal, a buffer layer covering at least one surface of the lithium metal, and a reaction layer located between the lithium metal and the buffer layer. The buffer layer includes a lithium intercalation material and a lithium-affinity material. The reaction layer is an alloy layer formed by the reaction of the buffer layer and lithium metal during the pressing process. Solid composite anodes are produced by dry coating of inorganic powder composed of lithium-intercalating and lithium-affinity materials onto the surface of metallic lithium and then pressing them. The lithiophilic material includes any one or a combination of at least two of zinc oxide, zinc sulfide, zinc chloride, aluminum oxide, magnesium oxide, tin oxide, or copper oxide; The lithium intercalation material includes any one or a combination of at least two of graphite, silicon, or carbon nanotubes; The reaction layer is a Li / M and Li / N alloy generated by the reaction of lithium metal and buffer layer material during the pressing process, wherein M is element C and / or Si, and N is any one or a combination of at least two of metals Zn, Al, Mg, Sn or Cu. The mass ratio of the lithium-intercalating material to the lithiophilic material is 1:(2-10).

2. The solid-state composite anode structure according to claim 1, characterized in that, The average particle size of the lithiophilic material is D50 < 60 nm.

3. The solid-state composite anode structure according to claim 1, characterized in that, The lithiophilic material is zinc oxide and / or zinc chloride.

4. The solid-state composite anode structure according to claim 1, characterized in that, The average particle size of the lithium intercalation material is D50 < 600 nm.

5. The solid-state composite anode structure according to claim 1, characterized in that, The lithium-intercalating material is graphite and / or carbon nanotubes.

6. The solid-state composite anode structure according to claim 1, characterized in that, When M is element C, the lithiation product of metallic lithium and lithium-intercalated materials is Li. x C y Where x:y = 1:1 to 1:24; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 ~ 1:

4.

7. The solid-state composite anode structure according to claim 6, characterized in that, When M is element C, the lithiation product of metallic lithium and lithium-intercalated materials is Li. x C y Where x:y = 1:1 to 1:6; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 ~ 1:1.

5.

8. The solid-state composite anode structure according to claim 1, characterized in that, When M is element Si, the lithiation product of the lithium metal and the lithium-intercalated material is Li. x Si, where x = 0.5~4.4; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 ~ 1:

4.

9. The solid-state composite anode structure according to claim 8, characterized in that, When M is element Si, the lithiation product of the lithium metal and the lithium-intercalated material is Li. x Si, where x = 0.5~3.25; the lithiation product of the lithium metal and the lithiophilic material is Li. m N n Where m:n = 1:1 ~ 1:1.

5.

10. The solid-state composite anode structure according to claim 1, characterized in that, The ratio of element N in the reaction layer and the buffer layer is x:y=1:1~1:5; the ratio of element M is m:n=1:1~1:

3.

11. The solid-state composite anode structure according to claim 10, characterized in that, The ratio of element N in the reaction layer and the buffer layer is x:y=1:1~1:3; the ratio of element M is m:n=1:1~1:

2.

12. The solid-state composite anode structure according to claim 1, characterized in that, The lithium metal includes any one of lithium sheets, lithium foil, or lithium strips.

13. A method for preparing a solid-state composite anode structure as described in any one of claims 1-12, characterized in that, The method includes the following steps: A solid composite anode structure is obtained by coating a mixture of lithium-intercalating and lithium-affinity materials onto one surface of metallic lithium and then pressing it. Alternatively, a mixture of lithium-intercalating and lithium-affinity materials can be coated onto one surface of lithium metal and pressed, then coated onto the other surface of lithium metal and pressed again to obtain a solid-state composite anode structure.

14. The preparation method according to claim 13, characterized in that, The mass ratio of the lithium-intercalating material to the lithiophilic material is 1:(2-10).

15. The preparation method according to claim 13, characterized in that, The mixing can be any one of ball milling, stirring, or vibration mixing.

16. The preparation method according to claim 15, characterized in that, The ball milling speed is 2 r / min-300 r / min.

17. The preparation method according to claim 16, characterized in that, The ball milling speed is 80 r / min-120 r / min.

18. The preparation method according to claim 15, characterized in that, The ball milling time is 2 min to 360 min.

19. The preparation method according to claim 18, characterized in that, The ball milling time is 30-60 minutes.

20. The preparation method according to claim 13, characterized in that, The coating method includes any one or a combination of at least two of the following: scraping, rolling, or brushing.

21. The preparation method according to claim 13, characterized in that, The coating is performed under an inert atmosphere.

22. The preparation method according to claim 21, characterized in that, The inert atmosphere includes any one or a combination of at least two of helium, neon, argon, krypton, or xenon.

23. The preparation method according to claim 13, characterized in that, The coating thickness of the mixture on the lithium metal surface is 1μm-10μm.

24. The preparation method according to claim 13, characterized in that, The mass ratio of the mixture to lithium metal is (10-100):

1.

25. The preparation method according to claim 24, characterized in that, The mass ratio of the mixture to lithium metal is (50-100):

1.

26. The preparation method according to claim 13, characterized in that, The pressing method is any one or a combination of at least two of the following: roller pressing, extrusion, or rolling.

27. The preparation method according to claim 13, characterized in that, The pressure for the pressing process is 1 MPa-20 MPa.

28. The preparation method according to claim 27, characterized in that, The pressure for the pressing process is 1MPa-5MPa.

29. The preparation method according to claim 13, characterized in that, The pressing process takes 5-100 seconds.

30. The preparation method according to claim 29, characterized in that, The pressing process takes 10-50 seconds.

31. The preparation method according to claim 13, characterized in that, The pressing process is carried out under an inert atmosphere.

32. The preparation method according to claim 31, characterized in that, The inert atmosphere includes any one or a combination of at least two of helium, neon, argon, krypton, or xenon.

33. A sulfide all-solid-state battery, characterized in that, The negative electrode in the sulfide all-solid-state battery is the solid-state composite negative electrode structure according to any one of claims 1-12.

34. The sulfide all-solid-state battery according to claim 33, characterized in that, The sulfide all-solid-state battery includes a positive electrode, a negative electrode, and a sulfide solid electrolyte disposed between the positive electrode and the negative electrode, wherein the negative electrode is a solid composite negative electrode structure as described in any one of claims 1-12, and the active material of the positive electrode is any one or a combination of at least two of layered oxides, polyanionic active materials, lithium-rich oxides, or spinel oxides.

35. The sulfide all-solid-state battery according to claim 34, characterized in that, The layered oxide includes LiNi 1-x-y Co x Mn y O2 and / or LiNi 1-x-y Co x Al y O2, where x = 0~1, y = 0~1.

36. The sulfide all-solid-state battery according to claim 34, characterized in that, The polyanionic active material includes any one or a combination of at least two of LiFePO4, LiMnPO4, or LiCoPO4.

37. The sulfide all-solid-state battery according to claim 34, characterized in that, The lithium-rich oxides include Li2MnO3 and / or Li2RuO3.

38. The sulfide all-solid-state battery according to claim 34, characterized in that, The spinel oxide includes LiMn2O4 and / or LiNi. 0.5 Mn 1.5 O2.

39. The sulfide all-solid-state battery according to claim 34, characterized in that, The sulfide solid electrolyte includes nLi₂S-(100-n)P₂S₅, Li₆PS₅X, or Li 11-a M 2-a P 1+a S 12 Any one or at least two of the following; where n = 0~100; a = 0~2; X is any one or at least two of Cl, Br or I; M is any one or at least two of Ge, Sn or Si.

Citation Information

Patent Citations

  • Lithium-aluminum alloy surface modified lithium negative electrode and solid-state battery thereof

    CN107068964A

  • Lithium metal negative electrode with interface modification layer and preparation method of lithium metal negative electrode

    CN115132958A